Implementasi Kebijakan Pembangunan Industri: Studi Kasus PT Pertamina (Persero) - Linda Fitriani; Pani Dwi Yanti; Naerul Edwin Kiky Aprianto; Anggi Barnia Safitri; Hasnaa U. Annabiilah (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This study examines the implementation of industrial development policies at PT Pertamina (Persero) as a strategic step in supporting national energy security and sustainable development. Referring to the National Industrial Development Master Plan (RIPIN) 2015-2035, this study highlights Pertamina's contribution to energy source diversification, operational efficiency, and strengthening industrial competitiveness. The analysis was conducted using a qualitative method based on literature studies with the Miles and Huberman model approach. The results of the study indicate that the RIPIN policy is implemented effectively through the development of renewable energy technology and increasing the capacity of energy infrastructure. However, several obstacles such as limited infrastructure, technology adoption, and global competition still affect the achievement of policy objectives. This study provides an important contribution in understanding the role of national energy companies in supporting an inclusive and environmentally friendly industrial development agenda.